RESPONSE OF CUSTOMIZED FERTILIZER ON WHEAT (TRITICUM AESTIVUM) UNDER CHHATTISGARH CONDITION - S. K. DWIVEDI; M. R. MESHRAM; N. PANDEY (The Bioscan, 2014)
A field experiment was conducted to evaluate the effect of customized fertilizer (CF) on wheat grown under clayey soils at IGKV, Raipur during winter season 2010-11 and 2011-12. The application of 150% dose of CF produced highest grain yield of wheat (4.4 t/ha), which was 28.27% higher than that of state recommended dose (120:60:40 kg NPK ha-1). The uptake of NPKS and Zn also increased due to application of 150% dose of CF. The highest net returns (Rs. 37,676 /ha) and benefit: cost ratio (2.7) was also obtained due to application of 150% CF, which was followed by application of 125 % CF and 100% CF, respectively.